STUDY OF CORAL BLEACHING MAPPING USING HIGH RESOLUTION IMAGES (A case study: The Water Area of PLTU Paiton Probolinggo) - Jaelani, Lalu Muhamad; Afifi , Zulfahmi (GEOID, 2016)
The rising temperature of Andaman Sea in May 2010 causing many Indonesia’s waters experienced 4°C temperature rise. This phenomena triggers coral bleaching in many Indonesia’s coastal area, one of them is Probolinggo beach. Probolinggo beach is a beach with very fascinating coral reefs, one of them is located near Paiton Power Plant area. Paiton plant unit is a power plant that is owned by PT. PJB which used to supply almost three of fourth part of the electricity in Java and Bali. PLTU Paiton is established at the seaside of Probolinggo beach, which has a coolant circulation system located adjacent to the sea. Coral bleaching mapping with remote sensing method with in situ data was used to detect the extent of areas experiencing coral bleaching. WorldView-2 Satellite Imagery was used with the processing performed on the blue bands and green bands which has the depth of water penetration. Water column correction is done to eliminate the effect of depth. Supervision classification is performed to get the alleged spot of coral bleaching. Classification results showed that the total area of the bleached corals from the five-point field observations with area of each point is 100m^2 is ± 726 m^2.The coral bleaching phenomenon in Paiton’s Power Plant coastal waters is caused by two main factors, the former is the rise of sea surface temperatures and the latter is the activity of Paiton itself. Dredging activities for the construction of new generating units and water discharge processing activities plant added the negative effect for the bleaching, aside from rising sea surface temperatures of ± 4° C.